The Development Model for Digital Transformation of Hotel in Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to 1) study the elements of the development model for digital transformation of hotel in Thailandand, 2) to develop the model of the digital transformation of hotel in Thailand. There are 3 steps of research: 1) study documentsand related research 2) develop a model for digital transformation of hotel in Thailand 3) analyzed the elements of thedevelopment pattern of the digital transformation of hotel in Thailand by analyzing the elements; The statistics used for dataanalysis were percentage, range, quartile, mean, standard deviation and elemental analysis. Research findings showed that 1)The study of the digital transformation of hotel in Thailand found that it consisted 3 important components: business model,operational process and customer experience. 2) Development of the digital transformation of hotel in Thailand found that thereare 5 main components: organization, information technology, innovation, digital transformation and business performance, andthe level of the digital transformation of hotel in Thailand overall are good.